2019
DOI: 10.26858/jppk.v5i2.10561
|View full text |Cite
|
Sign up to set email alerts
|

The portrait of spiritual intelligence and aggressiveness of university students

Abstract: Aggression is interpreted as a behavior that aims to hurt others physically and verbally. This study used quantitative approach through correlational method to find out the influence of spiritual intelligence (SQ) to the aggressiveness in university students. Students' aggressiveness was measured using adapted aggression questionnaire, while SQ was measured using the adapted spiritual intelligence scale. The sample technique used proportional random sampling technique and data analysis used regression test thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 24 publications
2
2
0
Order By: Relevance
“…In another study, the relationships between anger level, which form the basis of violent behaviors, and spiritual intelligence were examined and it was observed that the increase in spiritual intelligence reduced the anger level of the participants (Tarazoj et al, 2018). The results of some studies examining the relationships between spiritual intelligence and aggressive violent behaviors supporting the results obtained from this study show that there are negative relationships between spiritual intelligence and aggressive behaviors representing violence (Esmaili et al, 2021;Karimi & Mohammadi, 2020;Sakti & Alim, 2019). The results of a study examining the relationships between students' wellbeing and spirituality, by supporting the results obtained from this study show that there is a positive significant relationship between spirituality and well-being (Supriatna & Septian, 2021).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…In another study, the relationships between anger level, which form the basis of violent behaviors, and spiritual intelligence were examined and it was observed that the increase in spiritual intelligence reduced the anger level of the participants (Tarazoj et al, 2018). The results of some studies examining the relationships between spiritual intelligence and aggressive violent behaviors supporting the results obtained from this study show that there are negative relationships between spiritual intelligence and aggressive behaviors representing violence (Esmaili et al, 2021;Karimi & Mohammadi, 2020;Sakti & Alim, 2019). The results of a study examining the relationships between students' wellbeing and spirituality, by supporting the results obtained from this study show that there is a positive significant relationship between spirituality and well-being (Supriatna & Septian, 2021).…”
Section: Discussionsupporting
confidence: 86%
“…According to the results of a study examining the relationships between aggression behaviors and various types of well-being, again similar to the results obtained from the study, it was observed that there were significant negative relationships between well-being and aggression (Kaukiainen et al, 2001). The results of the study conducted to examine the effect of spiritual intelligence on students' aggressive behaviors supported the results obtained from this study and showed that spiritual intelligence encourages students to show ideal behavior and directs them to find a peaceful solution to all problems (Sakti & Alim, 2019). And according to the results of another study conducted with university students, it was observed that as the spiritual intelligence of the students increased, their aggressive behaviors decreased (Baloochi et al, 2018).…”
Section: Discussionsupporting
confidence: 83%
“…Recognition of students' abilities, both material and immaterial, is an internal factor that plays a huge role in the achievement of students' achievements. Recognition from superiors to subordinates for abilities and skills can provide multiple motivations to achieve company goals (Fajar Sakti & Alim, 2019). Recognition of self-existence can take the form of internal and external.…”
Section: The Relationship Of Potential and Character In Islamic Educa...mentioning
confidence: 99%
“…Subjective experience and spiritual consciousness have been extensively discussed in the religious perspective (Albursan et al, 2016;Hanefar et al, 2015), including the Christian perspective (Finka & Prasetya, 2018;Sakti & Alim, 2019). This section relates the Christian context with the trinity concept.…”
Section: Transcendental Phenomenologymentioning
confidence: 99%